Indentifikasi 4A (Attraction, Amenity, Accessibility dan Anciliary) dalam Pengembangan Pariwisata Berkelanjutan di Pantai Tanjung Pendam, Kabupaten Belitung: Indonesia - Yunisti Pratiwi (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2023)
The existence of tourists in a tourist attraction is the spearhead of the success of that tourist attraction, the number of tourist visits plays a strong role and actively contributes in improving the economy and people's welfare. The tourist attraction of Tanjung Pendam Beach, Belitung Regency has its own potential and is attractive to tourists who visit, but if the tourist attraction of Tanjung Pendam Beach does not carry out sustainable measures, it will result in being abandoned by visiting tourists. In this research study, a tourism sustainability strategy is provided using a review of the 4A main components in tourism, namely Attraction, Amenity, Accessibility and Anciliary. In the Qualitative Research Approach activities in data collection activities through observation, interviews and documentation. The results of this research show that the main components of 4A (Attraction, Amenity, Accessibility and Anciliary) are that the facilities are quite complete and good, but some facilities are still not utilized properly, and some facilities are outdated, damaged and neglected and require maintenance. By utilizing collaboration between other stakeholders, it can be a solution to help and make it easier to build and maintain tourist facilities so that they can be sustainable.